jejak digital Sosialisasi Jejak Digital Positif Sebagai Upaya Menyongsong Masa Depan Generasi Muda: Menanamkan Kesadaran Digital Sejak Dini untuk Masa Depan yang Gemilang - NIKEN SUKMAWATI, NIKEN SUKMAWATI; ELSA AZIA ULKHAQ; Alvia Muha, Reffi Achdan; Abdi Setiawan, M. Husni; Salam Solikhin, Muhamad Alfus; Ardika, Edho Atma (Nawasena Bhakti, 2025)
Along with the development of technology, many young people, especially generation Z, do not understand that technology can have a big impact on life. The activities they leave on social media leave traces called digital footprints. Many of them do not understand that it greatly affects the future. Socialization activities related to the theme presented, namely building a positive digital footprint to welcome the future, aim to educate, especially the younger generation, about the importance of maintaining a digital footprint as a provision for a bright future. Participants in the activity were grade VII students of SMP Islam Al-Aly. Through the delivery of the material presented, namely the understanding given about how to do good social media activities, data left behind in the digital world, especially on social media. This can affect a person's career. The current situation shows that 80% of companies recruit employees by looking at the digital footprint of prospective employees which is useful for knowing a person's character because the digital footprint is not far from a person's character, this has a very positive or negative impact on job opportunities. The activity method includes the stages of preparation, socialization and evaluation. The results of this activity show an increase in participants' understanding of the importance of managing a good digital footprint and being wiser in using social media. Which greatly affects career opportunities for the future. With this, it is hoped that awareness among participants will increase so that participants can be wiser in using social media so that their career opportunities will become better.